The Chemistry Mechanism in the Community Earth System Model Version 2 (CESM2). (17th April 2020) - Emmons, Louisa K.; Schwantes, Rebecca H.; Orlando, John J.; Tyndall, Geoff; Kinnison, Douglas; Lamarque, Jean‐François; Marsh, Daniel; Mills, Michael J.; Tilmes, Simone; Bardeen, Charles; Buchholz, Rebecca R.; Conley, Andrew; et al.
Abstract: The Community Earth System Model version 2 (CESM2) includes a detailed representation of chemistry throughout the atmosphere in the Community Atmosphere Model with chemistry and Whole Atmosphere Community Climate Model configurations. These model configurations use the Model for Ozone and Related chemical Tracers (MOZART) family of chemical mechanisms, covering the troposphere, stratosphere, mesosphere, and lower thermosphere. The new MOZART tropospheric chemistry scheme (T1) has a number of updates over the previous version (MOZART‐4) in CESM, including improvements to the oxidation of isoprene and terpenes, organic nitrate speciation, and aromatic speciation and oxidation and thus improved representation of ozone and secondary organic aerosol precursors. An evaluation of the present‐day simulations of CESM2 being provided for Climate Model Intercomparison Project round 6 (CMIP6) is presented. These simulations, using the anthropogenic and biomass burning emissions from the inventories specified for CMIP6, as well as online calculation of emissions of biogenic compounds, lightning NO, dust, and sea salt, indicate an underestimate of anthropogenic emissions of a variety of compounds, including carbon monoxide and hydrocarbons. The simulation of surface ozone in the southeast United States is improved over previous model versions, largely due to the improved representation of reactive nitrogen and organic nitrate compounds resulting in a lower ozone production rate than in CESM1 but still overestimates observations in summer. The simulation of tropospheric ozone agrees well with ozonesonde observations in many parts of the globe. The comparison of NOx and PAN to aircraft observations indicates the model simulates the nitrogen budget well. Plain Language Summary: The set of chemical reactions for tropospheric chemistry used in the Community Earth System Model version 2 (CESM2) has been updated significantly over CESM1 in the Community Atmosphere Model with chemistry (CAM‐chem) and Whole Atmosphere Community Climate Model (WACCM) configurations. The emissions used for the CESM2 simulations are documented here, with anthropogenic and biomass burning emissions based on the specified inventories for Climate Model Intercomparison Project 6 (CMIP6), and emissions of biogenic compounds, lightning NO, dust, and sea salt are calculated online and dependent on the simulated meteorology. Evaluation of the CAM‐chem and WACCM configurations of CESM2 with observations indicate an underestimate of anthropogenic emissions of a variety of compounds, including carbon monoxide and hydrocarbons. The updated chemistry leads to an improvement in the simulation of tropospheric ozone. Key Points: This paper fully documents the significant updates to the chemistry mechanisms in version 2 of the Community Earth System Model The new tropospheric chemistry scheme improves representation of isoprene oxidation as well as other ozone precursors over earlier versions The simulation of tropospheric ozone is improved in comparison to observations